2021
DOI: 10.1016/j.vaccine.2021.07.087
|View full text |Cite
|
Sign up to set email alerts
|

Immunisation of ferrets and mice with recombinant SARS-CoV-2 spike protein formulated with Advax-SM adjuvant protects against COVID-19 infection

Abstract: The development of a safe and effective vaccine is a key requirement to overcoming the COVID-19 pandemic. Recombinant proteins represent the most reliable and safe vaccine approach but generally require a suitable adjuvant for robust and durable immunity. We used the SARS-CoV-2 genomic sequence and in silico structural modelling to design a recombinant spike protein vaccine (Covax-19™). A synthetic gene encoding the spike extracellular domain (ECD) was inserted into a baculovirus backbon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 54 publications
2
51
0
Order By: Relevance
“…The vaccine is prepared from Spike protein ECD with an amino acid sequence corresponding to wild-type SARS-CoV-2 (Wuhan strain) together with some stabilizing mutations that is then codon optimized and expressed in insect cells using the baculovirus transfection system. This spike protein ECD antigen has been previously been shown to be immunogenic, protective, and safe in mice and ferrets in an Australian-developed vaccine called COVAX-19/SpikoGen [30] that has successfully passed phase III clinical trials and in October 2021 received emergency use authorization from the Iranian FDA [24]. This spike protein ECD formulated with an SWE adjuvant (NARUVAX-C19 vaccine) provided complete protection of Syrian hamsters against SARS-CoV-2 infection and prevented transmission to naïve animals placed in the same cage as the challenged animals [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vaccine is prepared from Spike protein ECD with an amino acid sequence corresponding to wild-type SARS-CoV-2 (Wuhan strain) together with some stabilizing mutations that is then codon optimized and expressed in insect cells using the baculovirus transfection system. This spike protein ECD antigen has been previously been shown to be immunogenic, protective, and safe in mice and ferrets in an Australian-developed vaccine called COVAX-19/SpikoGen [30] that has successfully passed phase III clinical trials and in October 2021 received emergency use authorization from the Iranian FDA [24]. This spike protein ECD formulated with an SWE adjuvant (NARUVAX-C19 vaccine) provided complete protection of Syrian hamsters against SARS-CoV-2 infection and prevented transmission to naïve animals placed in the same cage as the challenged animals [22].…”
Section: Discussionmentioning
confidence: 99%
“…The detailed methodology of obtaining recombinant Spike protein ECD has been described previously [24]. Brie y, the spike protein was identi ed from the SARS-CoV-2 genomic sequence in NCBI (access number: NC 045512) [25].…”
Section: Recombinant Spike Protein Vaccine Designmentioning
confidence: 99%
“…Clinical trials of NVX-CoV2737, which is formulated with the trimeric full-length SARS-CoV-2 S protein and Matrix-M1 adjuvant, have shown that this Matrix-M1-adjuvanted protein vaccine elicits CD4+ T-cell responses biased toward a Th1 phenotype [42,43]. The SARS-CoV-2 S protein formulated with Advax-SM, a combination adjuvant consisting of delta inulin polysaccharide particles (Advax™) and a TLR9-active oligonucleotide-CpG55.2, induced neutralizing antibodies in mice that could neutralize infection by the SARS-CoV-2 wildtype lineage B.1.319 and cross-neutralize the VOC Alpha (B.1.1.7), and protected ferrets against SARS-CoV-2 infection [44].…”
Section: Other Adjuvantsmentioning
confidence: 99%
“…Various generic platforms were used to develop the vaccines, such as using viral protein, Adenovirus-vectored vaccines, using an inactivated virus, mRNA, or RNA-based vaccine [184]. [184], [186][187][188][189][190][191][192][193][194][195][196]. aration, more than 983.1 million vaccine doses have been given worldwide [185].…”
Section: Vaccines Against Covid-19mentioning
confidence: 99%
“…Status of COVID-19 Vaccines until 30 November 2021[184],[186][187][188][189][190][191][192][193][194][195][196].…”
mentioning
confidence: 99%